A new Trichosalpinx (Orchidaceae: Pleurothallidinae) from the northern Pacific lowlands of Costa Rica - Fernández, Melania; Bogarín, Diego (Phytotaxa, 2011)
A new species of Trichosalpinx from the Pacific lowlands of Costa Rica is described and illustrated. Trichosalpinx reflexa, which is morphologically most similar to T. memor and T. ciliaris, is distinguished mainly by the narrow elliptical leaves, the glabrous sepals and the reflexed synsepal. Information about distribution, habitat and phenology of the new species is also provided.